A study in the basolateral amygdala of rats in short-term enriched environment: selection of reference genes and quantification of TrkB and ERK mRNA with RT-qPCR - Goh, Valerie Hui Hian (2016)
The brain is a highly plastic organ, liable to remodelling by several stimuli. Stress induces hypertrophy in the basolateral amygdala (BLA), culminating in increased risk to stress-related neuropsychiatric disorders. Environmental enrichment has been shown to confer resilience, affecting the brain in a reciprocal manner to stress. Though little is known about the mechanisms driving these alterations, a growing body of research indicate the involvement of brain-derived neurotrophic factor (BDNF). Remarkably little studies have investigated the roles of Tyrosine (or Tropomyosin) receptor kinase B (TrkB) and extracellular signal-regulated protein kinase (ERK), molecules associated with BDNF-signalling, in the divergent consequences of stress and EE. Hence in this study, the relative mRNA transcript abundances of TrkB and ERK following stress and EE were examined with RT-qPCR. As normalization is cardinal to obtaining meaningful data, several housekeeping genes were assessed before selection as reference genes. Results revealed that TrkB mRNA and ERK gene expression were not significantly altered by chronic immobilization stress (CIS) or EE, suggesting that TrkB and ERK may not be implicated in the differential effects of CIS and EE on neuronal morphology. However, definite conclusions were not reached, prompting further research of the roles of these molecules.